Analysis of the paleographic characteristics of viceroy manuscripts to the Municipal Chamber of ilha de Santa Catarina (1781 - 1789) - Mello, Daniel Morais de (2017)
This study aims to analyze paleographic aspects of three manuscripts authored by Viceroy Luís de Vasconcelos e Souza, dated from 1781 to 1789, highlighting the graphic, material and complementary aspects, which places the documents in its creation context and profiles the Portuguese writing of the time, according to the author's peculiarities. The manuscripts inform the Municipality of Santa Catarina Island the death of members of the royal family, ordering mourning period to all its districts. Follow the Normas Técnicas para Transcrição e Edição de Documentos Manuscritos are followed, as well as the guide to paleographic analysis of the work Noções de Paleografia e de Diplomática. Through critical observation of the manuscripts, it is made the description of the physical characteristics of the manuscripts with samples that expose the peculiarities in the writing of the Viceroy. It concludes that the manuscripts were written by skilled hands, although there are orthographic irregularities, and constitute on sources for further research.